La petite histoire du travail invisible (2019)
La petite histoire du travail invisible Voici notre vidéo sur les luttes féministes pour la reconnaissance du travail invisible! Elle est inaugurée en cette Journée nationale des centres de femmes du Québec #JNCF2019. Allez dans un centre près de vous pour continuer la lutte avec nous!Avec la participation L'R des centres de femmes du
Keywords: 1900-1999; 1960-1969; 2000 à aujourd'hui; 2010-2019; approches et analyses; discipline; foyer; groupes de femmes; histoire et politique; inégalités; justice sociale; militance; périodes historiques; ressource en ligne; sciences humaines; stage; systèmes d'oppressions; thématiques; travail; travail social

Reproductive and Sexual Health of People with Physical Disabilities: A Metasynthesis - Nguyen, Thi Tu An; Liamputtong, Pranee; Monfries, Melissa (Sexuality and Disability : A Journal Devoted to the Psychological and Medical Aspects of Sexuality in Rehabilitation and Community Settings, 2016)
This article provides an overview on reproductive and sexual health of people with physical disabilities in developed and underdeveloped countries from 1995 to 2011. Based on the metasynthesis approach, the authors reviewed 15 qualitative studies. These studies were searched using Medline, CINAHL, CINAHL (health), ProQuest Central, Google Scholar, Cochrane, Embase, Informit Health, Sciences Direct, Pubmed, Pubmed Health, AAHD (abstracts), ProQuest Journal (sexuality and disability) and were also manually searched. All studies were judged on their qualities using the Critical Appraisal Skills Programme. Reproductive health, sexual attractiveness and experiences, reproductive and sexual health knowledge, and dealing with reproductive and sexual health issues were four main themes that emerged from these studies. This paper proposes a new model to explain the factors that impacted the reproductive and sexual life of people with physical disabilities: internal and external factors. Implications for health and social care are discussed in light of the findings.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; capacitisme; care; cours; discipline; justice reproductive; médecine; métasynthèse; premier cycle; psychologie; périodes historiques; ressource en ligne; santé; sciences; sciences humaines; sex1920; sexualité; systèmes d'oppressions; thématiques; travail social

« Mon corps est une arme », des suffragettes aux Femen - Bard, Christine (Les Temps Modernes, 2014)
Keywords: 1900-1909; 1900-1999; 1910-1919; 2000 à aujourd'hui; 2010-2019; angleterre; approches et analyses; corps; cours; discipline; discours dominant; europe; histoire et politique; premier cycle; périodes historiques; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; travail social; trs1205

Un protocole d'application culturellement pertinent selon les sexes - Association des femmes autochtones du Canada (AFAC) (2011)
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; care; cours; discipline; droits des femmes*; droits des femmes* autochtones; féminisme autochtone; histoire et politique; pol4105; premier cycle; périodes historiques; québec; régions géographiques; santé; santé mentale; sciences humaines; sciences sociales; suicide; système colonial; systèmes d'oppressions; thématiques; traumatismes générationnels; travail social; violences